2014
DOI: 10.3109/13506129.2014.992515
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of semiautomatic quantification of left ventricular long axis shortening in systemic light-chain amyloidosis

Abstract: LAS was an independent predictor of survival within the first year and offers incremental information in patients with AL amyloidosis evaluated prior to specific treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…As atrioventricular valve plane motion reflects the longitudinal shortening of the left ventricle, previous observations also support the significance of its impairment in AL. The relative longitudinal axes shortening (LAS) and global longitudinal strain (GLS) are both independent predictors of survival [ 6 , 8 ]. Other innovative risk predictors in amyloidosis have emerged in cardiac magnetic resonance imaging, including late gadolinium enhancement, T1 mapping, and extracellular volume (ECV) which allow for a non-invasive semi-quantitative assessment of amyloid infiltration [ 18 ] and correlate with all-cause mortality [ 13 , 19 – 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As atrioventricular valve plane motion reflects the longitudinal shortening of the left ventricle, previous observations also support the significance of its impairment in AL. The relative longitudinal axes shortening (LAS) and global longitudinal strain (GLS) are both independent predictors of survival [ 6 , 8 ]. Other innovative risk predictors in amyloidosis have emerged in cardiac magnetic resonance imaging, including late gadolinium enhancement, T1 mapping, and extracellular volume (ECV) which allow for a non-invasive semi-quantitative assessment of amyloid infiltration [ 18 ] and correlate with all-cause mortality [ 13 , 19 – 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal systolic deformation of the left ventricle (LV) is known to be strongly associated with survival in AL amyloidosis [ 6 – 8 ]. Atrioventricular plane displacement contributes approximately 60% to the LV stroke volume [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…33 The correlation of TMAD with echo-based values of global systolic function such as strain, the strain rate, and the ejection fraction (EF) was generally high, and the discriminatory ability of TMAD to identify patients with certain diseases such as amyloidosis and hypertrophic cardiomyopathy was also high. 36,37 An association of TMAD with hard clinical outcomes, for which none of these studies was powered, was ambiguous. 33,34,37,39 When the required times were measured, these were generally less than 15 seconds per echocardiographic view.…”
Section: Previous Studies Regarding Speckle-tracking-based Displacementmentioning
confidence: 99%
“…36,37 An association of TMAD with hard clinical outcomes, for which none of these studies was powered, was ambiguous. 33,34,37,39 When the required times were measured, these were generally less than 15 seconds per echocardiographic view. 33,38 Buss et al 33 also examined lower-quality images and found that in patients with reduced image quality (n = 67), TMAD acquisition could be performed more often than strain imaging (67 versus 43; P < .001).…”
Section: Previous Studies Regarding Speckle-tracking-based Displacementmentioning
confidence: 99%
See 1 more Smart Citation